Neuroadaptive changes in brain structural–functional coupling among pilots - Chen, Xi; Meng, Qingbin; Song, Qingsong; Xu, Peiran; Zhang, Shicong; Huang, Donglin; Chu, Qi; Fan, Jiamin; Luo, Cheng; Li, Xiuyi (Frontiers in Neuroscience, 2025)
BackgroundInvestigating the neural mechanisms underlying pilots’ brains is crucial for enhancing aviation safety. However, prior research has predominantly focused on identifying structural and functional differences in the brain, while the relationship between structure and function remains insufficiently elucidated.MethodsThis study collected T1-weighted structural magnetic resonance imaging (MRI), resting-state functional MRI (rs-fMRI), and diffusion tensor imaging (DTI) data from 47 pilots and 38 matched controls. Structural–functional coupling (SFC) strength was quantified using the Structural Decoupling Index (SDI) based on graph signal processing (GSP). Functional connectivity was further decomposed into structurally coupled and decoupled components, with subsequent group comparisons conducted at the regional brain level.ResultsCompared to controls, pilots exhibited significantly higher SDI values in several brain regions, including the left and right middle frontal gyri, left precentral gyrus, inferior temporal gyrus, left posterior superior temporal sulcus, right superior and inferior parietal lobules, left visual cortex, and right basal ganglia, indicating reduced SFC in these areas. In contrast, enhanced coupling was observed in the bilateral inferior frontal gyri, left paracentral lobule, and left insula. Notably, pilots showed increased decoupled functional connectivity (d-FC) between the left cuneus and right insula, as well as between the right insula and the left medial occipital cortex, accompanied by a reduction in coupled functional connectivity (c-FC). Importantly, the strength of decoupled functional connectivity between the right insula and the left medial occipital cortex was positively correlated with total flight hours.ConclusionThese findings suggest that prolonged flight experience may induce neuroplastic changes in regional SFC within the brains of pilots. This work provides novel insights into the neural adaptations associated with flight training and may contribute to the refinement of pilot selection and training protocols aimed at improving aviation safety.